(untitled) (Research, Society and Development, 2021)
The study objective was to analyze the vegetation structure of the anthropic primary forest fragment in the municipality of Paragominas in Para. The vernacular name , the circumference of the height of 1.3 m above the ground - CAP ≥ 31.5 cm (DBH ≥ 10 cm) and height (H) of all individuals of tree species were collected in 12 sampling units of 20 mx 50 m , randomly distributed in the area. The sample sufficiency was evaluated by adjusting the generated species-area curve between the area of the parcels and the number of new species. The sample was recorded 320 individuals classified into 29 botanical families, 44 genera and 46 species defined and 4 morphospecies. To the horizontal structure, the species with the highest abundance was Inga alba (9.7%). Eschweilera coriacea stood out with 13.31% of dominance in the study area, which helped it to become the species with the highest importance value of the area with 8.59% market share. With an average occurrence of 41 species / ha of floristic composition, the area of forest fragment showed a diversity of species expressed by the Shannon-Weaner index of 3.29, considered low compared with forests in the same region. As for classification of species in ecological groups, the late pioneer and secondary species are groups equivalent to 30% of the floristic composition, characterizing that under the forest canopy dominated by shade-tolerant and species belonging to the early secondary group, contributed 28 %, showing an advanced stage of ecological succession. By outo hand, the occurrence of 30% of late secondary and pioneer can be explained by logging occurred in the fragment area. Regarding the type of life in the forest fragment 90% of the species are trees, bushes 8% and 2% palm trees, with strong predominance of trees.